INFLUENCE OF FACEBOOK AND ELECTRONIC DEVICES ON SECONDARYSCHOOL STUDENTS’ PERFORMANCE IN ISLAMIC STUDIES IN ILORIN WESTLOCAL GOVERNMENT AREA, KWARA STATE - Yunus, Aliyu (Religions' educator, 2020)
Facebookisasocialmediumplatformwhereinteractionisbeingmadebydifferentpeoplearoundtheglobe.However,theuseofelectronicdeviceimprovestheskillsofteachersandmakeslearningeasierforthestudentsinameaningfulway.ThisstudyexaminedtheInfluenceofFacebookandelectronicdevicesontheacademicperformanceofstudentsinIslamicStudiesinIlorinWestLocalGovernmentArea,Nigeria.However,asurveydesignwasadoptedforthisstudy.Thequestionnairewasusedtocollectdatafrom200respondentsinaseniorsecondaryschoolinIlorinWestLocalGovernmentArea,Nigeria.Thevalidityoftheinstrumentwasacquiredaftertheseriesofamendmentsbythreemeasurementandevaluationexperts.Forthereliabilityofaninstrument,apre-testwasconductedforthequestionnaireandtheresultswereusedtocalculatethereliabilitycoefficientwhichwas0.74.Chi-squarewasusedtotestthetwoResearchHypothesisgeneratedinthestudy.TheSPSSvision23wasusedfordataanalysis.However,FacebookfindingsofthisstudyrevealedthatmajorityofstudentsspenttheirtimeonFacebook.Itfurthershowedthatthemajorityofthelearnersstronglybelievedthatusinganelectronicdevicesuchassmartphonetoteachinclassimprovestheiracademicperformance,especiallyinIslamicStudies.Itwasrecommendedthat;government,teachersandparentsshouldworkhandinhandtoenlightenthestudentsonhowtheusagetheFacebookwillhelptheiracademic endeavor.